The Basis of Multicultural Islamic Education in Kudus: Study of the Thoughts of Shaykh Ja'far Shadiq in developing Archipelagic Tradition of Islam - Afif, Muhammad; Amiruddin, Muh (Al Hikmah: Journal of Education, 2024)
The basis of multicultural Islamic education was developed by scholars of the Walisongo generation, such as that developed by Sheikh Ja'far Shodiq in Kudus. This educative tradition continues to be preserved by the majority Muslim community of Nahdliyyin Kudus until now. Trough qualitative research, this study found two important aims, namely: (a) the Hindu-Buddhist-Islamic cultural acculturation model of Sheikh Ja'far Shodiq and (b) the philosophy of multicultural Islamic education, Sheikh Ja'far Shodiq. the findings are that the concept of multicultural Islamic education of Sheikh Ja'far Shadiq in Kudus is based on democratic, dialogical, educative, persuasive patterns, and pluralist views. Besides, many efforts have been made by the Kudus community to develop the concept of Sheikh Ja'far Shadiq's multicultural Islamic education into Nusantara Islamic tradition or moderate Islam manifested in some traditions, such as in the tradition of sambatan, bersih desa, dan joint kenduren.